2021
DOI: 10.1371/journal.pone.0260662
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Zn-Aspartate in comparison with ZnSO4 and L-Aspartate in amelioration of drought stress in maize by modulating antioxidant defence; osmolyte accumulation and photosynthetic attributes

Abstract: Human population is exceeding beyond the carrying capacity of earth resources and stresses like water shortage faced by the plants is jeopardizing the food security. Current research study was aimed to investigate the potentials of Zn-Aspartate (Zn-Asp), Zn-Sulphate (ZnSO4) and L-Aspartate (L-Asp) to be used as osmolytes and role of various levels of these chemicals in combating drought stress in maize plants in Punjab, Pakistan. Study was performed on two plots corresponding to drought and controlled environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Previous research showed that arginine and aspartate play roles in plants under drought stress ( Hasanuzzaman et al., 2018 ; You et al., 2019 ; Ali et al., 2021 ). In roots of WS pine seedlings, levels of arginine and aspartate increased, compared with those in roots of WW pine seedlings, respectively ( Figure 2B ), but untargeted metabolomics analysis showed that levels of L-aspartic acid in roots and needles of WS pine seedlings reduced, compared with those in WW pine seedlings, respectively ( Table S10 , positive ion mode).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that arginine and aspartate play roles in plants under drought stress ( Hasanuzzaman et al., 2018 ; You et al., 2019 ; Ali et al., 2021 ). In roots of WS pine seedlings, levels of arginine and aspartate increased, compared with those in roots of WW pine seedlings, respectively ( Figure 2B ), but untargeted metabolomics analysis showed that levels of L-aspartic acid in roots and needles of WS pine seedlings reduced, compared with those in WW pine seedlings, respectively ( Table S10 , positive ion mode).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the negative impacts of different stresses at any of the growth stages, different methods or techniques are being employed ( Ali et al., 2019 ; Ali et al., 2020a , Ali et al., 2020b , Ali et al., 2020c ; Perveen et al., 2021 ; Saeed et al., 2023a , Saeed et al., 2023b ), including the screening of plant genotypes with improved germination potential ( Ali et al., 2016 , Ali et al., 2018 ), agronomic practices ( Lamichhane and Soltani, 2020 ), and use of chemicals (organic and inorganic ones) through different ways at different growth stages ( Ali et al., 2018 ; El Sabagh et al., 2019 ; Ali et al., 2021 ; Shehzad et al., 2022 ). Seed priming not only improves seed germination to obtain a good crop stand but also induces tolerance in plants to various stresses at later growth stages ( Lutts et al., 2016 ; Noman et al., 2018a , Noman et al., 2018b ; Nawaz et al., 2020 ; Ali et al., 2020a ; Habib et al., 2021 ; Arun et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%